Changes in Patterns of Intensity-modulated Radiotherapy Verification and Quality Assurance in the UK. Issue 8 (August 2016) - Abolaban, F.; Zaman, S.; Cashmore, J.; Nisbet, A.; Clark, C.H.
Abstract: Aims: Between 2012 and 2014 the number of patients treated in the UK with intensity-modulated radiotherapy (IMRT) techniques increased significantly. One reason for this was the radiotherapy innovation fund for the centres in England. Before the announcement of the fund, a survey of radiotherapy centres was carried out in 2012 which collected data on IMRT uptake, obstacles to implementation, equipment used, delivery techniques and verification methods. A repeat survey was carried out in 2014 to identify key changes to IMRT quality assurance and verification practices. Materials and methods: An online questionnaire was sent out to all 65 UK radiotherapy centres in the summer of 2012 and again in the summer of 2014. Questions covered background and equipment, machine tolerance and quality assurance, machine-based verification, software-based verification and future plans. Results: There have been significant changes in the delivery techniques used for IMRT, with more than twice as many centres reporting the use of volumetric-modulated arc therapy techniques in 2014 compared with 2012. This has been combined with an increase in Monte Carlo-based algorithms in treatment planning systems. In 2012 all centres reported the need to carry out machine-based measurements for IMRT plan verification, dropping to 93% in 2014. Nineteen per cent of centres now report making only one measurement per month for prostate plans and 8% of breast plans never have physical measurements. Most centres use detector arrays for quality assurance measurement (86% in 2012 and 91% in 2014), but a significant number still use film and/or ionisation chambers (51% and 41%). In the analysis of these measurements there has been an increase in the use of tighter criteria. There has been a significant increase in the use of software for verification from 63% in 2012 to 95% in 2014. All centres reported that they needed further resources in order to efficiently achieve the quality assurance required for the number of patients planned to be treated in their centre. Conclusions: The increased numbers of patients being treated with IMRT has meant that there have been significant changes in the way that quality assurance is carried out. These have been mainly in the reduction of measurements and the increase in software-based verification. However, quality assurance is still a significant burden and still has an effect on the numbers of patients who can be treated with IMRT. Highlights: Current status of IMRT quality assurance. Changes in IMRT quality assurance over a 2 year timeframe. Impact of the Radiotherapy Innovation Fund on the quality assurance needed for IMRT.